Chaotic Oscillations in H2O2 - H2SO4 - Pt Electrochemical System. (10th December 2015) - Mukouyama, Yoshiharu; Hara, Daisuke; Kawasaki, Hirokazu; Kikuchi, Mitsunobu; Yamada, Yuri; Nakanishi, Shuji
Abstract : The current due to the H2 O2 reduction at Pt electrodes in H2 SO4 solutions shows a period-1 oscillation, named oscillation A. This work reports that the oscillation changes into complex oscillations such as a mixed-mode, chaotic, and period-n oscillations when Na2 SO4 or K2 SO4 is added to the solutions. The alkali metal ions originated from the salts, namely, Na + and K + ions, increase the local pH at the electrode surface during the H2 O2 reduction, as has been reported before ( ECS Transactions 64 (2015) 49). However, the complex oscillations are found not to be caused by the increase in the local pH. It is possibly that a non-covalent interaction between adsorbed OH, that is the reaction intermediate of the H2 O2 reduction, and the alkali metal ions plays a crucial role for the appearance of the complex oscillations. The clarification of the origin of the complex oscillations needs further study.